The Cost Analysis of Human Resources Development Stunting Prevention - Hairuddin; Reza Aril Ahri; Nurmiati Muchlis; Masriadi; Nurul Susanti (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The basic health research report in 2018 stated that stunting in children in Indonesia hadreached 30.8%, some public helath centre have not got a particular allocation of funds for the developmentof maternal and child health workers to prevent stunting. It can slow down the program to accelerate thereduction in stunting rates that has been promoted by the government. analyzing direct and indirect costs ofdeveloping human resources for stunting prevention in Enrekang District, Indonesia. Material and Methods:The research method used is qualitative research with an analytic survey approach. The data used in thisstudy are secondary data and primary data obtained from interviews with related parties. Results: This typeof qualitative research was collected using in-depth interview techniques. The results show that the directcost selection and recruitment is IDR. 10,484,000, indirect cost is IDR. 1,800,000 and Total cost IDR.12,284,000; the direct cost for one-time training and human resource development is IDR. 9,500,000 and theindirect cost is IDR. 33,600,000.Conclusion: Reaching the Human Resources Development (HRD) budgetof IDR. 304,086,533 can only effectively reduce stunting by 3.1% so that achieving the 2023 target of 15%is difficult to meet. The government concerned is expected to increase the HRD Fund to achieve the 2023target.